Pengaruh Metode Penanaman Lingkar Berjajar Pada Pertumbuhan Tanaman Jagung Manis (Zea Mays Saccharata). - Lutfy Ditya Cahyanti; Use Etica (Jurnal Penelitian Pertanian Terapan, 2020)
The experiment aims to know the effect of The off-row circle planting method on the growth of sweet corn. This research was conducted in the Sub District of Siman, Ponorogo, with altitude 140 asl and textured clay grumosol soil types. The research used a randomized block design (CBD) with 4 kinds of planting spaces included C1 = 8 plant / (60x80) cm2, C2 = 16 plant / (60x80) cm2, C3 = 12 plant/ (60 x 80) cm2, C4 = 1 plant/ (60 x 80) cm2, C5 = 1 plant/ (60 x 80) cm2 with mowing. Each experimental unit was repeated 5 times so that there were 25 units. The observation was done at 21,28, 35, 42 and DAP (the day after planting). Some vegetative growth traits of sweet corn were determined as plant height (cm), the number of leaves (leaf plant-1), leaf area (m2) and leaf area index, fresh weight (g) and dry weight (g). Row circle planting method affected the fresh weight and dry weight of sweet on 49 DAP, sweet corn with 1 plant/ (60 x 80) cm2 with mowing treatments showed the higher value and significantly different with other treatments, with 803 g for fresh weight and 7,70 g for dry weight.